The effects of previous summer drought and fertilization on winter non-structural carbon reserves and spring leaf development of downy oak saplings - Wang, Xiaoyu; Schönbeck, Leonie; Gessler, Arthur; Yang, Yue; Rigling, Andreas; Yu, Dapao; He, Peng; Li, Maihe (Frontiers in Plant Science, 2022)
It is still unknown whether the previous season drought and fertilization will affect the winter non-structural carbohydrate (NSC) reserves, spring leaf development, and mortality of trees next year. We, therefore, conducted an experiment with Quercus pubescens (downy oaks) saplings grown under four drought levels from field capacity (well-watered; 25% volumetric water content) to wilting point (extreme drought; 6%), in combination with two fertilizer treatments (0 vs. 50 kg N/ha/year) for one growing season. We measured the pre- and post-winter NSC, and over-winter NSC consumption in storage tissues (i.e. shoots and roots) following drought and fertilization, and recorded the spring leaf phenology, leaf biomass, and mortality next year. The results showed that, irrespective of drought intensity, carbon reserves were abundant in storage tissues, especially in roots. Extreme drought did not significantly alter NSC levels in tissues, but delayed the spring leaf expansion and reduced the leaf biomass. Previous season fertilization promoted shoot NSC use in extreme drought-stressed saplings over winter (showing reduced carbon reserves in shoots after winter), but it also showed positive effects on survival next year. We conclude that: (1) drought-stressed downy oak saplings seem to be able to maintain sufficient mobile carbohydrates for survival, (2) fertilization can alleviate the negative effects of extreme drought on survival and recovery growth of tree saplings.